Alkaline fermentation of Bambara groundnut (Vigna subterranean L. Verdc. ) as dawadawa-like African food condiment - Buys, E.M. (Elna Maria) (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.